Association of adherence to a 3 month cardiac rehabilitation with long‐term clinical outcomes in heart failure patients. (9th February 2022) - Nakanishi, Michio; Miura, Hiroyuki; Irie, Yuki; Nakao, Kazuhiro; Fujino, Masashi; Otsuka, Fumiyuki; Aoki, Tatsuo; Yanase, Masanobu; Goto, Yoichi; Noguchi, Teruo
Abstract: Aims: Although comprehensive cardiac rehabilitation (CCR) is recommended for patients with heart failure (HF), participants often show low adherence. The aim of this study was to evaluate the association of CCR completion and response with long‐term clinical outcomes. Methods and results: We screened 824 HF patients who participated in a 3 month CCR programme and underwent baseline assessment, including cardiopulmonary exercise testing (CPX). After excluding 52 participants who experienced all‐cause death or HF hospitalization within 180 days, long‐term outcomes were compared between those who attended 3 month follow‐up assessment including CPX (completers) and those who did not (non‐completers). We also compared the prognostic value of the changes in peak oxygen uptake (VO2 ) vs. quadriceps muscle strength (QMS) during the 3 month CCR programme. Among the 772 study patients, there were no significant differences in baseline characteristics, including left ventricular ejection fraction, B‐type natriuretic peptide levels, and peak VO2, between the completers ( n = 561) and non‐completers ( n = 211), except for a higher age (63.2 ± 14.2 vs. 59.4 ± 16.2 years; P = 0.0015) and proportion of females (27% vs. 17%; P = 0.0030) among the completers. During a median follow‐up of 55.4 months, the completers had lower rates of the composite of all‐cause death or HF hospitalization (34.4% vs. 44.6%; P = 0.0015) and all‐cause death (16.9% vs. 24.6%; P = 0.0037) than the non‐completers. After adjustment for prognostic baseline characteristics, including age and sex, CCR completion was associated with 34% and 44% reductions in the composite outcome and all‐cause death, respectively. Among the completers, peak VO2 and QMS increased significantly (8.9 ± 15.8% and 10.5 ± 17.9%, respectively) over 3 months. Patients who had an increase in peak VO2 ≥ 6.3% (median value) during the CCR programme had significantly lower rates of the composite outcome (27.0% vs. 33.8%; P = 0.048) and all‐cause mortality (10.0% vs. 17.4%; P = 0.0069) than those who did not. No statistically significant difference was observed in the composite outcome (30.5% vs. 30.4%; P = 0.76) or all‐cause mortality (13.0% vs. 14.4%; P = 0.39) between those with and without an increase in QMS ≥8.3% (median value). Conclusions: In HF patients who participated in a 3 month CCR programme, its completion was associated with lower risks of subsequent HF hospitalization and death. Within the group of patients who completed the programme, the improvement in exercise capacity, but not in skeletal muscle strength, over the 3‐month period was associated with better outcomes. These findings highlight the importance of the post‐CCR follow‐up assessment, including CPX, to identify a patient's adherence and response to the CCR programme.